MEDICÍNSKA BYROKRACIA A DEHUMANIZÁCIA SUBJEKTU V ZBIERKE IMUNITA OD M. FERENČUHOVEJ - Cepková Feješová, Zuzana Cepková Feješová (Conversatoria Litteraria, 2019)
The contribution focuses on the latest book produced by the contemporary Slovak authoress Mária Ferenčuhová. From all the different aspects of her poetry the article explores the phenomenon of dehumanization of the patient’s self. This dehumanization is conceived as a criticism of Cartesian dualism: transformation of the human subject into an impersonal object. This act of criticism is created through the poetic thematization of corporeity which is pushed into the foreground due to sickness, old age and treatment within a hospital environment ruled over by medical bureaucracy. As a result of this reification, the verses reveal a deep internal tension concerning its subject. Indeed, one of the signs of the objectification of the subject is the adoption of a sterile vocabulary from the ambient of medical bureaucracy which reduces human beings into mere objects of medical treatment.